RNA expression of TLR10 in normal equine tissues - Tarlinton, Rachael E.; Alder, Lauren; Moreton, Joanna; Maboni, G.; Emes, Richard D.; Tötemeyer, Sabine (BioMed Central, 2016)
Background: Toll like receptors are one of the major innate immune system pathogen recognition systems. There is little data on the expression of the TLR10 member of this family in the horse.